Lactic Acidosis as a Result of Iron Deficiency - Finch, Clement A.; Gollnick, Philip D.; Hlastala, Michael P.; Miller, Louise R.; Dillmann, Erick; Mackler, Bruce (The Journal of Clinical Investigation, 1979)
Iron-deficient rats have an impaired work performance, even when their anemia is corrected by exchange transfusion. Muscle activity is associated with a higher blood lactate concentration than is observed in iron-replete animals. The accumulation of lactate is a result of excessive production as lactate clearance from the blood was shown to be unaffected. By adjusting the work load to a lower level, it was possible to divide iron-deficient animals into two groups, one capable of continued treadmill running and another in which animals stopped before 20 min. In the former, blood lactate concentration reached a plateau at moderate levels, whereas it continued to increase in the latter until the animal stopped running. Levels of α-glycerophosphate oxidase in skeletal muscle mitochondria were found to be much lower in the second group (P < 0.001). Lactate infusion into normal animals was shown to interfere with work performance, and maintenance of a normal pH in iron-deficient and iron-replete animals did not prevent the impairment in work associated with high blood lactate concentrations. Additional evidence was obtained that energy substrate (blood glucose and free fatty acids, muscle glycogen) was adequate in irondeficient animals. Oxygen tension in their vena caval blood was higher than in controls. Furthermore, the in situ behavior of electrically stimulated gastroenemius and soleus muscles appeared similar to that of control animals. Because the stimulation of the single muscle in the iron-deficient animal did not result in appreciable elevation of blood lactate and did not show impaired contractility further supported the hypothesis that the elevation of blood lactate caused the decreased work performance. It is concluded that iron deficiency by a depletion in the iron-containing mitochondrial enzyme, α-glycerophosphate oxidase, impairs glycolysis, resulting in excess lactate formation, which at high levels leads to cessation of physical activity.